Potret Sikap Moderat Muslim Merauke : Studi Etnografi di Kampung Kuprik Distrik Semangga Kabupaten Merauke Papua Selatan - Mohammad Nailun Ni’am; Moch. Bachrurrosyady Amrullah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The research aims to describe the characteristics of moderate attitudes and the underlying processes that shape them within the community's socio-religious life. Data were collected through observation, in-depth interviews, and document analysis. The findings reveal that moderate attitudes are reflected in openness, interreligious cooperation, active tolerance, and respect for diversity. The formation of these attitudes is influenced by multicultural life experiences, local wisdom values, the roles of religious and community leaders, and religious education that instills tolerance from an early age. Social media also plays a positive role as a means of education and interfaith communication. Moderate attitudes have become not only a social norm but also a community identity that preserves harmony and solidarity. These findings are expected to serve as a model for strengthening religious moderation in other multicultural communities across Indonesia.